Photocatalytic degradation of methylene blue dye under direct sunlight irradiation using SnO2 nanoparticles - Sagadevan, Suresh; Anita Lett, J.; Alshahateet, Solhe F.; Fatimah, Is; Weldegebrieal, Getu Kassegn; Le, Minh-Vien; Leonard, Estelle; Paiman, Suriati; Soga, Tetsuo (Elsevier, 2022)
In this work, we report the hydrothermal synthesis, characterization, and photocatalytic activity of SnO2 nanoparticles (NPs) towards methylene blue (MB) dye. The synthesized sample was characterized using X-ray diffraction (XRD), Fourier transform infrared (FTIR), ultraviolet–visible (UV–Vis), scanning electron microscopy (SEM), transmission electron microscopy (TEM), and N2-sorption isotherm techniques. Results show that synthesized sample was tetragonal structure with an optical bandgap, average crystallite size, and degree of crystallinity equal to 3.67 eV, 21 nm, and 70%, respectively. The impacts of dye initial concentration, catalyst dose, and oxidant addition on the sunlight-assisted photodegradation performance were investigated. Degradation of 97% was achieved in 2 h of irradiation utilizing 10 ppm dye initial concentration and 40 mg catalyst dose at natural pH and in the absence of any oxidant. However, in the presence of the H2O2 oxidant complete removal was observed in just 90 min without changing other parameters.